Admitting Service and Outcome for Small Bowel Obstruction. Issue 4 (April 2022) - Thacker, Christopher; Lauer, Claire; Nealon, Kathleen; Walker, Charles; Factor, Matthew
Introduction: Small bowel obstruction (SBO) is a common admission diagnosis. Prior research has shown improved length of stay and time to operation for SBO patients on surgical services (SS) compared to medical services (MS). This study evaluates the impact of admitting service on readmission and mortality. Methods: A 12-year retrospective cohort study of patients ≥18 years old, admitted with SBO to either a MS or SS within one health care system was performed. Clinicodemographic characteristics and admission details were extracted and reviewed. Statistical analyses performed included the Student's t-test, chi-square, and multivariable regression. Results: The study included 7921 patients, of which 3862 (48.8%) were admitted to a SS. No significant clinicodemographic differences existed between the groups except SS patients were more likely to have cancer (23.3% vs 15.2%, P < .0001) and to be within a 30-day post-operative period (9.4% vs 1.8%, P < .0001). On multivariable analysis, admission to a SS was associated with a decreased admission mortality (OR .70), 30-day mortality (OR .42), and 180-day mortality (OR .42). 30-day readmissions (OR .54) and 180-day readmission (OR .43) were also significantly decreased for SS patients. In patients requiring a procedure during admission, there was significantly decreased admission mortality (OR .684), 30-day mortality (OR .470), 180-day mortality (OR .431), 30-day readmission (OR .63), and 180-day readmission (OR .50). Conclusion: In patients with SBO, admission to a SS confers decreased odds of readmission and mortality compared to MS. Future studies are needed to understand the management decisions potentially underlying these differences. These findings may help better define admission pathways and improve outcomes.